Inclusive Wealth Report 2018 - Managi, Shunsuke; Kumar, Pushpam (Taylor & Francis, 2018)
The Inclusive Wealth Index provides important insights into long-term economic growth and human well-being. The Index measures the wealth of nations through a comprehensive analysis of a country's productive base and the country's wealth in terms of progress, well-being and long-term sustainability. It measures all assets which human well-being is based upon, in particular, produced, human and natural capital to create and maintain human well-being over time.